Prevalence of metabolic syndrome in patients with psoriasis: A prospective, observational, descriptive study from a tertiary health-care center in South India - Deepika Lunawat; Aditya Kumar Bubna; Anandan Sankarasubramaniam; Mahalakshmi Veeraraghavan; Sudha Rangarajan; Adikrishnan Swaminathan (Wolters Kluwer Medknow Publications, 2017)
Background: Psoriasis is a chronic inflammatory disorder which of late has been significantly linked with metabolic syndrome (MS). Objective: To assess the association between psoriasis and MS and evaluate specific disease characteristics predisposing for the development of MS. Materials and Methods: We performed a prospective, observational, descriptive study with 207 adult patients with various types of psoriasis. Results: MS was found in 49.8% of psoriatic patients. It was more prevalent after 40 years of age with a female preponderance (P = 0.000). Smoking (P = 0.0320) and alcohol consumption (P = 0.025) were significant contributing factors for the development of MS in our study population. No association for the same was reflected with parameters such as psoriasis type, lifestyle behavior, family history, and other associated systemic disease. Conclusion: A definite association does exist between psoriasis and MS. Patients with psoriasis should be periodically screened for MS and managed appropriately utilizing an interdisciplinary approach.